Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Editorial: The ACCOBAMS Survey Initiative (ASI): implementing large scale surveys for marine megafauna in the Mediterranean and Black Seas - Simone Panigada; Nejla Bejaoui; Oliver Boisseau; Ayaka Amaha Öztürk; Vincent Ridoux (Frontiers in Marine Science, 2024)

Density and abundance estimates of cetaceans in the Black Sea through aerial surveys (ASI/CeNoBS) - Romulus-Marian Paiu; Ana Cañadas; Ayhan Dede; Galina Meshkova; Dumitru Murariu; Ayaka Amaha Ozturk; Dimitar Popov; Arda M. Tonay; Costin Timofte; Natia Kopaliani; Pavel Gol’din; Simone Panigada (Frontiers in Marine Science, 2024)
Introduction Population abundance is amongst the most basic and crucial parameters for the assessment of conservation status of any species. Three species of odontocetes, all represented by local subspecies, inhabit the Black Sea: the Black Sea common dolphin Delphinus delphis ponticus , the Black Sea bottlenose dolphin Tursiops truncatus ponticus , and the Black Sea harbour porpoise Phocoena phocoena relicta . Their populations are threatened by multiple factors, including overfishing of their prey, bycatch, pollution and epizootics. Despite this, there are no basinwide estimates for any cetacean species in the Black Sea. Methods In 2019, a systematic study was carried out under the EU CeNoBS project. Six strata were designed in the waters of Bulgaria, Georgia, Romania, Türkiye and Ukraine, covering most of territorial and offshore waters, which were surveyed between June 19 and July 4. A line transect distance sampling approach was used, following predefined transects within each stratum, achieving a 5% coverage of the surveyed area. A total of 7,344 kilometres of transects were surveyed recording a total of 1,744 cetacean sightings. Design-based abundance estimates were obtained using a Multiple Covariate Distance Sampling (MCDS) approach. Model-based abundance estimates were also derived using a Generalized Additive Models (GAM) approach, linking species sightings with a number of environmental covariates (e.g., bathymetric features, sea surface temperature, chlorophyll-a) over a grid of 10x10 km. Results and discussion The uncorrected (for perception and availability bias) estimates obtained through the model-based analysis were 108,283 (CV=0.07) common dolphins, 22,720 (CV=0.15) bottlenose dolphins and 93,808 (CV=0.06) harbour porpoises. These aerial surveys yielded the first insights on overall abundance, density and distribution, providing current regional baseline values and density maps for all three cetacean species of the Black Sea during the summer months, to be used for the elaboration of effective conservation measures and to address national and international requirements.

Evaluation of the exposure of the Mediterranean biodiversity to marine litter: the ASI – plastic busters MPAs projects connection - Massimo Perna; Carlo Brandini; Michele Bendoni; Chiara Lapucci; Francois Galgani; Simone Panigada; Ana Cañadas; Cristina Panti; Maria Cristina Fossi (Frontiers in Marine Science, 2024)
A number of marine species in the Mediterranean are threatened by the presence of several pressure factors, which include climate change, collisions with vessels, entanglement and ingestion of marine litter, especially plastic. Risk reduction policies can only be conceived starting from an accurate analysis of the exposure to such pressure factors. To estimate spatial abundance of both marine species and plastic litter and to assess the exposure risk, a two-stage analysis approach was applied, using aerial survey data from the ACCOBAMS Survey Initiative (ASI), in synergy with the Plastic Busters MPAs (PB MPAs) project. First, a detection function was fitted to observation data to obtain detection probabilities for individuals, then a Generalized Additive Model (GAM) was employed to estimate the spatial distribution of relative abundance, based on survey observations. A bivariate Local Indicator of Spatial Association (LISA) was then applied to the maps of relative abundance to derive risk maps of exposure of marine species to marine litter. The maps, obtained with a spatial resolution of about 10 km, allow us to identify areas with the highest neighboring abundance of taxa and marine litter, in particular for the MPAs studied by the PB MPAs project, which include the North-Western Mediterranean (Pelagos Sanctuary and Tuscan Archipelago), the Ionian and Aegean Sea (Zakynthos), and the Strait of Sicily (Cabrera Archipelago).

The ACCOBAMS survey initiative: the first synoptic assessment of cetacean abundance in the Mediterranean Sea through aerial surveys - Simone Panigada; Nino Pierantonio; Hélder Araújo; Léa David; Nathalie Di-Méglio; Ghislain Dorémus; Joan Gonzalvo; Draško Holcer; Sophie Laran; Giancarlo Lauriano; Romulus-Marian Paiu; Morgane Perri; et al. (Frontiers in Marine Science, 2024)
The “ACCOBAMS Survey Initiative” (ASI) is a pilot programme aimed at establishing an integrated and coordinated monitoring system for cetaceans across the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and contiguous Atlantic (hereafter “ACCOBAMS”) area. Conducted in coordination with Mediterranean coastal countries, it supports the implementation of European and regional policies, in particular the EU Marine Strategy Framework Directive and the Ecosystem Approach process. In summer 2018, a synoptic survey was conducted across the Mediterranean Sea and contiguous Atlantic area, combining visual monitoring from aircrafts with visual and passive acoustic monitoring from vessels. Species density and abundance were estimated through design-based approach in a line-transect sampling framework. Based on data arising from the aerial survey only, uncorrected design-based abundance was obtained for striped (N=426,744, CV=0.13), common (N=65,359, CV=0.4), bottlenose (N=63,333, CV=0.17), and Risso´s dolphins (N=26,006, CV=0.3), Cuvier’s beaked whales (N=2,929, CV=0.4) and long-finned pilot whales (N=5,540 CV=0.4). A merged category of either striped or common dolphins resulted in 212,828 individuals (CV=0.26). Fin whales abundance of 1,749 animals (CV=0.3) was corrected for both availability and perception biases and resulted in 3,282 (CV=0.31). The ASI survey offers an overall picture of the distribution and abundance of cetaceans throughout the Mediterranean basin, providing robust estimates to be considered as a baseline for future regional systematic monitoring programmes. The ASI survey is the first step towards establishing a long-term monitoring program across the entire ACCOBAMS area, and, as such, it sets the basis for further future basin-wide monitoring efforts using systematic, shared, coordinated and comparable methods. The information gathered will further enhance knowledge on cetacean status, facilitating the development of informed conservation and mitigation measures, as well as supporting the implementation of international obligations. Furthermore, the outcomes of this survey will support both place- and threat-based conservation efforts in the ACCOBAMS area, through the identification of Important Marine Mammal Areas and Cetacean Critical Habitats. Here the results of the ASI survey are presented and discussed alongside proposed management and conservation actions aimed at ensuring the persistence of cetacean populations in the region.

Acoustic estimates of sperm whale abundance in the Mediterranean Sea as part of the ACCOBAMS Survey Initiative - Oliver Boisseau; Jonathan Reid; Conor Ryan; Anna Moscrop; Richard McLanaghan; Simone Panigada (Frontiers in Marine Science, 2024)
Acoustic surveys for sperm whales ( Physeter macrocephalus ) were conducted in the Mediterranean Sea in summer 2018 as part of the vessel-based component of the ACCOBAMS Survey Initiative (ASI). Equal-spaced zigzag transects provided uniform coverage of key sperm whale habitats and were surveyed using a towed hydrophone array deployed from a research vessel at speeds of 5-8 knots. A total of 14,039 km of tracklines were surveyed in the western basin, Hellenic Trench and Libyan waters, with an acoustic coverage of 10% realised for sperm whales. During these surveys, 254 individual sperm whales were detected on the trackline, with an additional 66 individuals off-track. Sperm whales were only seen ten times on-track, with an additional 16 off-track sightings. Estimates of slant range to echolocating whales were used to derive density estimates through both design- and model-based distance sampling methodologies. An acoustic availability of 0.912 (sd = 0.036) was derived from via published models. When correcting for availability bias, a design-based abundance estimates of 2,673 individuals (95% CI 1,739-4,105; CV = 0.21) was derived for the surveyed blocks, which incorporated most known sperm whale habitat in the Mediterranean Sea. The equivalent model-based estimate was 2,825 whales (2,053-3,888; CV = 0.16). Over 97% of detected whales were in the western basin, with highest densities in the Algerian and Liguro-Provencal Basins between Algeria and Spain/France. In the eastern basin, detections were sparse and concentrated along the Hellenic Trench. A density surface modelling (DSM) exercise identified location and benthic aspect as being the most instructive covariates for predicting whale abundance. Distance sampling results were used in a power analysis to quantify the survey effort required to identify population trends. In the most extreme scenario modelled (10% per annum decline with decennial surveys), the population could have dropped by 90% before the decline was identified with high statistical power. Increasing the regularity of surveys would allow population trends to be detected more expediently. Mediterranean sperm whales are listed as Endangered on the IUCN’s Red List and the need for urgent conservation measures to reduce injury and mortality remains paramount for this unique sub-population.

PelaSIG, a QGIS plugin for marine megafauna census: application to the aerial ACCOBAMS Survey Initiative dataset - Manon Nivière; Ariane Blanchard; Oussama Jraifi; Olivier Van Canneyt; Ghislain Dorémus; Jérôme Spitz; Bruno Mansoux; Simone Panigada; Sophie Laran (Frontiers in Marine Science, 2024)
The distribution of wild animals and their monitoring over large areas raises many logistical and technical difficulties that hinder the collection of observation data. The use of Geographic Information Systems (GIS) has increased significantly in recent years. QGIS, an open-source GIS software dedicated to the processing of geospatial data, enables the development of dedicated plugins for specific workflows. The open-source PelaSIG plugin has been developed in Python for QGIS 3 to facilitate and standardise the different steps before and after distance sampling surveys. It brings together a set of tools for survey preparation, automatic data checking, visualisation and presentation of survey effort and sightings to provide an adapted workflow. This plugin is currently designed to process dedicated aerial datasets collected with the SAMMOA software during marine megafauna surveys (i.e., marine mammals, seabirds, elasmobranchs, sea turtles, etc.). Here, we first describe the different tools already available, and then, we present an application with the dataset from the aerial survey of the ACCOBAMS Survey Initiative (ASI) conducted in 2018 over the Mediterranean Sea and using a multi-target protocol.

Distribution patterns of marine megafauna density in the Mediterranean Sea assessed through the ACCOBAMS Survey Initiative (ASI) - Ana Cañadas; Nino Pierantonio; Hélder Araújo; Léa David; Nathalie Di Meglio; Ghislain Dorémus; Joan Gonzalvo; Draško Holcer; Sophie Laran; Giancarlo Lauriano; Morgane Perri; Vincent Ridoux; et al. (Frontiers in Marine Science, 2023)
The ACCOBAMS Survey Initiative (ASI) is the first synoptic large-scale survey of the entire ACCOBAMS Area and as such it plays a key role in filling the current gaps in our biological and ecological knowledge of large vertebrate species occurring in the region. Data gathered during the ASI were analyzed in a distance sampling surface-modelling framework to assess the summer distribution, densities and patterns, as well as to investigate the correlates of these parameters, for large vertebrate species and taxa in the Mediterranean Basin. Static and dynamic explanatory variables, including water depth (m), distance to depth contours (km), distance to canyons and seabed slope (km), sea surface temperature (°C), mixed layer depth (m) and levels of chlorophyll-a (mg/l), were considered to predict density and compute its variance spatially at a resolution of 10x10 km. A strong longitudinal gradient from low densities in the east to high densities in the west is shared by most taxa. In addition, several taxa also showed a less marked latitudinal gradient varying in direction according to species, and finally, a few of them exhibited patchy distributions.

Estimating the impact of ship strikes on the Mediterranean fin whale subpopulation - Maxime Sèbe; Léa David; Frank Dhermain; Sophie Gourguet; Bénédicte Madon; Denis Ody; Simone Panigada; Hélène Peltier; Linwood Pendleton (Ocean & Coastal Management, 2023)

Basin-wide estimates of loggerhead turtle abundance in the Mediterranean Sea derived from line transect surveys - Andrew DiMatteo; Ana Cañadas; Jason Roberts; Laura Sparks; Simone Panigada; Olivier Boisseau; Anna Moscrop; Caterina Maria Fortuna; Giancarlo Lauriano; Draško Holcer; Hélène Peltier; Vincent Ridoux; et al. (Frontiers in Marine Science, 2022)
Loggerhead turtles are a globally vulnerable species of marine turtle. Broad-scale patterns of distribution and abundance can provide regional managers a tool to effectively conserve and manage this species at basin and sub-basin scales. In this study, combined aerial and shipboard line transect survey data collected between 2003 and 2018 were used to estimate distribution and abundance throughout the Mediterranean Sea. Approximately 230,000 linear kilometers of survey effort, from seven different surveying organizations were incorporated into a generalized additive model to relate loggerhead density on survey segments to environmental conditions. Two spatial density models estimating loggerhead density, abundance, and distribution were generated – one a long-term annual average covering 2003-2018 and another covering the summer of 2018, when a basin-wide aerial survey, the Agreement on the Conservation of Cetaceans of the Black Sea, Mediterranean Sea and Contiguous Atlantic Area Survey Initiative, was performed. Both models were adjusted for availability bias using dive data from loggerhead turtles tagged with time depth recorders. Mean abundance for the long-term average model was estimated as 1,201,845 (CV=0.22). The summer 2018 abundance estimate was 789,244 turtles and covered a smaller area than the long-term average. These estimates represent the first basin-wide estimates of abundance for loggerhead turtles in the Mediterranean not based on demographic models. Both models predicted similar distributions, with higher abundance predicted in the northern Adriatic Sea, central Mediterranean basin, Tyrrhenian Sea, and south of the Balearic Islands. Lower densities were predicted in the eastern Mediterranean Sea and the Aegean Sea. The highest density areas generally did not coincide with previously established adult loggerhead turtle foraging areas, which are typically neritic, indicating the models are predominantly predicting oceanic distributions, where most of the survey effort occurred. Juvenile loggerhead turtles are predominantly oceanic and comprise most of the population, but care must be taken when using these models as they may not accurately predict distribution of neritic foraging areas, where subadult and adult loggerheads can often be found. Despite this limitation, these models represent a major step forward for conservation planning and understanding basin-wide distribution and abundance patterns of this species.

The Important Marine Mammal Area Network: A Tool for Systematic Spatial Planning in Response to the Marine Mammal Habitat Conservation Crisis - Michael J. Tetley; Gill T. Braulik; Caterina Lanfredi; Gianna Minton; Simone Panigada; Elena Politi; Margherita Zanardelli; Giuseppe Notarbartolo di Sciara; Erich Hoyt (Frontiers in Marine Science, 2022)
The Important Marine Mammal Areas (IMMAs) initiative was launched by the Marine Mammal Protected Areas Task Force of the International Union for the Conservation of Nature in 2016, as a response to a conservation crisis in the protection of marine mammals and wider global ocean biodiversity. IMMAs identify discrete portions of habitat that are important for one or more marine mammal species, and that have the potential to be delineated and managed for conservation. They are identified by scientific experts during regional workshops, on the basis of satisfying one or more of eight criteria that capture critical aspects of marine mammal biology, ecology and population structure. Candidate IMMAs undergo independent scientific review prior to being accepted, and then are publicly available via a searchable and downloadable database and a dedicated online e-Atlas. Between 2016 and 2021, eight expert workshops - engaging more than 300 experts - have resulted in the identification of 173 IMMAs located in 90 countries or territories, across a third of the globe. IMMAs identified to date provide important habitats for 58 of the 131 recognized marine mammal species. Around two-thirds of all IMMAs (65%) were identified on the basis of important habitat for a marine mammal species that is threatened on the IUCN Red List. Approximately 61% of IMMA surface areas occur within Exclusive Economic Zone waters, while 39% fall within areas beyond national jurisdiction. The Task Force undertook implementation planning exercises for IMMAs in Palau (Micronesia), the Andaman Islands (India) and the Bazaruto Archipelago and Inhambane Bay (Mozambique), engaging with a range of stakeholders including government and management bodies. IMMAs are increasingly being utilized in environmental impact assessments, marine planning exercises and in international, national and supra-regional conservation, policy and management initiatives, including the Convention on Migratory Species and Convention on Biological Diversity, as well as the design and management of Marine Protected Areas (MPAs) and the extension of MPA networks. The Task Force is working toward completing a global network of IMMAs that will contribute the scientific information needed to fulfill the current collective goal of protecting 30% of the ocean by 2030.

Ecotoxicological Characterization of Type C Killer Whales From Terra Nova Bay (Ross Sea, Antarctica): Molecular Biomarkers, Legacy, and Emerging Persistent Organic Contaminants - Cristina Panti; Juan Muñoz-Arnanz; Letizia Marsili; Simone Panigada; Matteo Baini; Begoña Jiménez; Maria Cristina Fossi; Giancarlo Lauriano (Frontiers in Marine Science, 2022)
Among killer whale forms, type C is a fish-eating form and is the most common in the Ross Sea. In the austral summer 2015, a study was conducted to evaluate the toxicological hazard these marine mammals face in the Antarctic ecosystem. Seven biopsy samples were collected from adult individuals (five males and two females) in the surroundings of the Italian Research Station Mario Zucchelli, Terra Nova Bay, by remote dart sampling from the pack ice. The accumulation levels of persistent organic pollutants (POPs) such as legacy (DDTs, PCBs, and HCB) and emerging (PBDEs and DP) were measured. Moreover, the protein expression of cytochrome P450 (CYP1A1 and 2B) and the mRNA level variations of the peroxisome proliferator-activated receptors α and γ ( PPAR α - γ) and the estrogen receptor α ( ER α), aryl hydrocarbon receptor ( AhR ), and Cyp1a were evaluated. Twenty PCB congeners, six DDTs, HCB, three HCHs, and fourteen brominated BDEs and DP-syn and anti-isomers were analyzed on freeze-dried blubber biopsy samples by GC-MS. The protein expression was evaluated by Western Blot and the mRNA levels were quantified by quantitative real-time PCR. The average abundance pattern for the contaminants was DDTs > PCBs > HCB > HCHs ≈ PBDEs >> DP. Contaminant levels resulted to be lower when compared to the existing data from the Antarctic type C killer whales from the McMurdo Sound (Ross Sea) and those reported for fish-eating killer whales worldwide. The mRNA levels of the five target genes were successfully quantified, but no statistical correlation was found with POP levels, suggesting that either the low levels of quantified POPs in blubber may not significantly affect the biological responses investigated, or that other stressors could contribute to the alterations of the molecular biomarkers. Although the results showed a lower risk related to contamination compared to more impacted areas, this study provides baseline data for the conservation of this species in an area with high ecological value, recently declared as the largest Marine Protected Area in Antarctica, where pollutants should remain at minimum levels despite increasing multiple stresses existing in the region.

Skin in the game: Epidermal molt as a driver of long‐distance migration in whales - Robert L. Pitman; John W. Durban; Trevor Joyce; Holly Fearnbach; Simone Panigada; Giancarlo Lauriano (Marine Mammal Science, 2020)
Long‐distance migration in whales has historically been described as an annual, round‐trip movement between high‐latitude, summer feeding grounds, and low‐latitude, winter breeding areas, but there is no consensus about why whales travel to the tropics to breed. Between January 2009 and February 2016, we satellite‐tagged 62 antarctic killer whales ( Orcinus orca ) of four different ecotypes, of which at least three made short‐term (6–8 weeks), long‐distance (maximum 11,000 km, round trip), essentially nonstop, migrations to warm waters (SST 20°C–24°C), and back. We previously suggested that antarctic killer whales could conserve body heat in subfreezing (to −1.9°C) waters by reducing blood flow to their skin, but that this might preclude normal (i.e., continuous) epidermal molt, and necessitate periodic trips to warm waters for routine skin maintenance (“skin molt migration,” SMM). In contrast to the century‐old “feeding/breeding” migration paradigm, but consistent with a “feeding/molting” hypothesis, the current study provides additional evidence that deferred skin molt could be the main driver of long‐distance migration for antarctic killer whales. Furthermore, we argue that for all whales that forage in polar latitudes and migrate to tropical waters, SMM might also allow them to exploit rich prey resources in a physiologically challenging environment and maintain healthy skin.

Combining multiple visual surveys to model the habitat of deep‐diving cetaceans at the basin scale - Auriane Virgili; Matthieu Authier; Oliver Boisseau; Ana Cañadas; Diane Claridge; Tim Cole; Peter Corkeron; Ghislain Dorémus; Léa David; Nathalie Di‐Méglio; Charlotte Dunn; Tim E. Dunn; et al. (Global Ecology and Biogeography, 2019)
Aim Deep‐diving cetaceans are oceanic species exposed to multiple anthropogenic pressures including high intensity underwater noise, and knowledge of their distribution is crucial to manage their conservation. Due to intrinsic low densities, wide distribution ranges and limited presence at the sea surface, these species are rarely sighted. Pooling data from multiple visual surveys sharing a common line‐transect methodology can increase sightings but requires accounting for heterogeneity in protocols and platforms. Location North Atlantic Ocean and Mediterranean Sea. Time period 1998 to 2015. Major taxa Ziphiidae; Physeteriidae; Kogiidae. Methods About 1,240,000 km of pooled effort provided 630 sightings of ziphiids, 836 of physeteriids and 106 of kogiids. For each taxon, we built a hierarchical model to estimate the effective strip width depending on observation conditions and survey types. We then modelled relative densities in a generalized additive modelling framework. Geographical predictions were limited to interpolations identified with a gap analysis of environmental space coverage. Results Deeper areas of the North Atlantic gyre were mostly environmental extrapolation in the predictions, thereby highlighting gaps in sampling across the different surveys. For the three species groups, the highest relative densities were predicted along continental slopes, particularly in the western North Atlantic Ocean where the Gulf Stream creates dynamic frontal zones and eddies. Main conclusions Pooling a large number of surveys provided the first basin‐wide models of distribution for deep‐diving cetaceans, including several data‐deficient taxa, across the North Atlantic Ocean and the Mediterranean Sea. These models can help the conservation of elusive and poorly known marine megafauna.

Life‐history tables of the Mediterranean fin whale from stranding data - Massimo Arrigoni; Piero Manfredi; Simone Panigada; Lorenzo Bramanti; Giovanni Santangelo (Marine Ecology, 2011)
The conservation of long‐lived species requires extensive, in‐depth knowledge of their population structure and vital rates. In this paper we examine the structure of the Mediterranean fin whale ( Balaenoptera physalus ) population based on the available mortality figures from European stranding network databases compiled over the past 22 years. Such data has enabled us to lay out a first life‐history (mortality) table of the population using a simple age‐structured demographic model with three life‐tables: calf, immature and mature. Our results reveal a high mortality rate in the first stage of life (77% per year), which decreases during the immature stage and falls further during the mature adult stage. In addition, we have calculated the corresponding life expectancies at birth (e 0 ), at entry in the immature stage (e 1 ) and at maturity (e 2 ) under different hypotheses on survival at the maximum age of 90 years (s 90 ) ranging between 0.1 and 3% of newborns still alive. The life expectancy at birth (e 0 ) at the lower bound of the chosen range (s 90 = 0.001) is about 6 years, entry in the immature stage (e 1 ) is 8.2 years, and entry in the mature stage (e 2 ) is about 15.6 years. This large increase is the consequence of the higher mortality in the first two stages compared with the mature one. The life expectancies are 10.1, 14.3, and 37.8 years for s 90 at the upper bound of the chosen range (s 90 = 0.03). The resulting population intrinsic growth rates (r) ranged between −1.3. and +1.7 per year. High juvenile mortality patterns imply that the stationary reproductive value (the number of female offspring produced by each female after a given age x) at the start of maturity reaches a value about seven times higher than at birth. Only optimistically high survival patterns of older individuals would allow positive intrinsic growth rates, thereby enhancing the chances of the population survival.

MEDITERRANEAN FIN WHALE'S (BALAENOPTERA PHYSALUS) RESPONSE TO SMALL VESSELS AND BIOPSY SAMPLING ASSESSED THROUGH PASSIVE TRACKING AND TIMING OF RESPIRATION - Maddalena Jahoda; Claudio L. Lafortuna; Nicoletta Biassoni; Carla Almirante; Arianna Azzellino; Simone Panigada; Margherita Zanardelli; Giuseppe Notarbartolo Di Sciara (Marine Mammal Science, 2003)
A bstract Twenty‐five fin whales ( Balaenoptera physalus ) were individually studied in their Ligurian Sea feeding grounds to describe and measure short‐term responses to the close approach of a fast‐moving inflatable craft from which biopsy samples were collected. Passive tracking was performed with a new technique based on simultaneous determination of (1) position of the observation vessel, (2) laser‐measured distance between the target animal and the observation vessel, and (3) azimuth of the target animal with respect to the observation vessel. Tracking was combined with timing of the surfacing intervals. Two different swimming‐surfacing patterns supposed to be related to feeding and traveling, respectively, were observed. Supposed feeding whales reacted to disturbance by changing their behavior into traveling. Two different avoidance strategies were performed simultaneously by the whales: travel at increased velocity and reduction of the time spent at the surface. After the disturbance ceased, the surfacing activity never completely reverted to predisturbance conditions during one hour of post exposure control and supposed feeding behavior appeared to be suspended indefinitely. Our results suggest the need for whale watching regulations in the Ligurian Sea, particularly as far as presumed feeding whales are concerned.